Breat care in breast-feeding mothers: the benefit of therapeutic laser applied by physiotherpasts - X. Bodenstein; E.C. van Vuuren; G. Joubert (AOSIS, 2014)
Breast-feeding is promoted worldwide as it has many health and nutritional benefits.